Hydrology and the management of watersheds - Brooks, Kenneth N.; Ffolliott, Peter F.; Magner, Joseph A. (Ames, Iowa : Wiley-Blackwell, 2012)
"Hydrology and the Management of Watersheds, Fourth Edition is a major revision and restructuring of this popular text. The content and scope have been improved and condensed, covering basic concepts and the fundamental aspects of hydrology and hydrologic processes, as well as methods and applications for managing watersheds. Examples throughout the book emphasize the use of web sites and access to the internet to acquire data, update methods and models, and to apply the latest technology to cope with issues of land and water use and climatic variability and change. Beyond the university classroom, Hydrology and the Management of Watersheds discusses land and water resource issues with implications for professionals in hydrology and watershed management in the United States, North America and beyond "--
Hydrologic cycle and the water budget -- Precipitation -- Evaporation, interception, and transpiration -- Infiltration, pathways of water flow and recharge -- Streamflow measurement and analysis -- Groundwater and groundwater-surface water exchange -- Soil erosion processes and control -- Sediment supply, transport, and yield -- Fluvial processes and implications for stream management -- Water-quality characteristics -- Managing wildland watersheds -- Managing riparian communities and wtelands -- Watershed management issues -- Socioeconomic considerations in integrated watershed management -- Tools and emerging technologies.
Revised edition of: Hydrology and the management of watersheds / Kenneth N. Brooks, et al. 2003.
Includes bibliographical references and index.
Print version record.
Keywords: Watershed management; Watersheds; Hydrology; Hydrology; TECHNOLOGY & ENGINEERING -- Environmental -- Water Supply; Watershed management; Watersheds; TECHNOLOGY & ENGINEERING -- Environmental -- Water Supply; TECHNOLOGY & ENGINEERING -- Hydraulics; Hydrology; Watershed management; Watersheds; Electronic books